â€œJapanese Ants (Tenebrio Molitor) Stabilize Blood Sugar Levels For Diabeticsâ€: The Current Issue OF Herbal Medicine In Indonesia" - Asirotul Marifah Marifah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
There are still many of our people who have never heard or even seen the shape of the Japanese ants, so sometimes people consume Japanese ants with different doses between people with each other and even some who consume Japanese ants are not appropriate doses because they want to get well soon. The purpose of research to know the relationship between consumption patterns of Japanese ants and blood sugar levels of people with diabetes mellitus. The design of this study is correlational analytic with crossectional approach. Variables of this research there are two that is the pattern of consumption of Japanese ants as an independent variable and blood sugar levels as the dependent variable. The population of this study was all patients with diabetes Mellitus who had suffered > 5 years who consumed Japanese ants in Grinting Village Karangjeruk Village Jatirejo Subdistrict Mojokerto regency as many as 10 respondents. in the sampling of researchers using total sampling technique. Data collection with an observation sheet of Japanese ant consumption and blood sugar level. The result of the research showed that most of the respondents consume Japanese ants regularly as much as 6 respondents (60%) and most respondents have blood sugar level in the normal category that is between 100-125 mg/dl as many as 6 respondents (60%). Consumption Japanese ants can routinely lower blood sugar levels of people with diabetes mellitus because ants contain enzymes that can keep blood sugar levels diabetics.